Tolerability of Bowel Preparation and Colonoscopy in IBD Patients: Results from a Prospective, Single-Centre, Case-Control Study. Issue 4 (7th November 2020) - Bezzio, Cristina; Schettino, Mario; Manes, Gianpiero; Andreozzi, Paolo; Arena, Ilaria; Della Corte, Cristina; Costetti, Martina; Devani, Massimo; Omazzi, Barbara Federica; Saibeni, Simone
Abstract: Background: Endoscopy plays a fundamental role in the management of patients with inflammatory bowel disease (IBD). Aims: to prospectively evaluate the tolerability and efficacy of bowel preparation and colonoscopy in ulcerative colitis (UC) and Crohn's disease (CD) patients compared to subjects participating in a colorectal cancer population screening program. Methods: consecutive enrolment of CD and UC patients and screening subjects (SS) undergoing colonoscopy. Bowel preparation was done by split dose of 2 L PEG-ELS + simethicone. We recorded endoscopic, clinical, and demographic features; cleanliness rating using the Boston Bowel Preparation Scale (BBPS); sedation doses. Bowel-preparation tolerability, discomfort and pain during colonoscopy were assessed using a Visual Analogue Scale (VAS) from 0 to 100 mm. Results: 63 UC (mean age 49.9 ± 14.9 yrs), 63 CD (mean age 44.0 ± 14.0 yrs) and 63 SS (mean age 59.9 ± 6.3) enrolled. Bowel preparation was similarly tolerated in UC, CD and SS (p=0.397). A complete colonoscopy was similarly performed in UC (59/63, 93.7%), CD (58/63, 92.1%) and SS (60/63, 95.2%) (p=0.364). The BBPS did not show significant differences between UC (6.2 ± 1.6), CD (6.1 ± 1.3) and SS (6.2 ± 1.4) (p=0.824). The need to increase sedation doses was significantly higher in CD (24/63, 38.1%) and UC (16/63, 25.4%) than in SS (4/63, 6.3%) (p<0.0001). Conclusions: bowel preparation is equally tolerated and efficacious in IBD patients and in healthy screening subjects. In IBD, higher sedation doses are needed to guarantee an equally tolerated colonoscopy. Lay Summary: Bowel preparation, done by split-dose of 2 liters, was equally tolerated and efficacious in Crohn's disease and ulcerative colitis patients and in healthy subjects undergoing colonoscopy. In IBD patients, higher sedation doses are needed to guarantee an equally tolerated colonoscopy.